Annual, seasonal and spatial differences in the growth rate of Baltic cod larvae and early juveniles in relation to zooplankton biomass fluctuations in 2006-2014 - Spich Katarzyna; Fey Dariusz Piotr (Oceanological and Hydrobiological Studies)
It is an acknowledged theory that a faster growth rate, determined by various environmental drivers, may boost the survival of larval and juvenile fish. In this study we examined the differences in the growth rate of larval and juvenile cod (age 2 – 136 d; SL: 4.1 – 39.2 mm) between the years 2006 and 2014, sub-areas of the Baltic Sea (Bornholm Basin, BB; Słupsk Furrow, SF; Gdansk Basin, GB), and seasons (spring and summer). The average growth rate for all specimens was 0.25 mm/d, with significantly lower values between 2012 and 2014 than between 2006 and 2011. A reduction in zooplankton biomass, especially the large zooplankton fraction, was observed after the 2006–2008 period, which was related to the prevailing temperature conditions in the surface layers. The reduction in zooplankton biomass was accompanied by changes in the structure of zooplankton: less T. longicornis, C. hamatus, and Pseudocalanus spp., and more Acartia spp. The results suggest that the inter-annual differences observed in zooplankton biomass and structure are likely responsible for the observed reduction in the growth rate of cod larvae between 2012 and 2014 compared to the years between 2006 and 2011. The growth rate reduction could be one of the reasons for the decline in the recruitment of eastern Baltic cod between the years 2013 and 2015, after the high recruitment years of the period 2011-2012.